Evaluating The Economic Benefits for Local Communities’ Climate-Resilient Marine Protected Areas - Fernandes, Ruban Baltazar; Rajan, S.S. (International Journal of Accounting and Economics Studies, 2025)
In India, the fishing industry directly employs about a million people. Additionally, it creates indirect jobs in related industries, including salt, ice, basketry, net making, boat construction, fish processing, and transportation. India has a high chance of improving its fish production if it has enough money and access to contemporary technologies. A larger percentage of the resource's potential could be used for financial gain. The fishing communities make up the rural coastal sector. The advancement of the social and economic standing of the fishing communities is a prerequisite for the growth of the coastal sector. Even though the fishing industry contributes significantly to the nation's wealth and export earnings, the bulk of fishermen are low-income individuals who live below the poverty line. Such a fantastic hunting sport calls for expertise and understanding. Since the beginning of time, a group of individuals or a community of individuals—typically those that fall into the ignored or marginalized category- have participated in this hunting process. Given the circumstances, a thorough analysis of the socioeconomic standing of marine fishing communities in the Gulf of Mannar region—including problems and trends—would be necessary. Thus, this study project has been started. This researcher believes it is appropriate to take on the current project because the previous researchers did not address these topics with methodological rigor in their respective research endeavors.
Keywords: Fisheries; Marine Environment; Economic Benefits